Modafinil May Alleviate Poststroke Fatigue: A Randomized, Placebo-Controlled, Double-Blinded Trial. Issue 12 (December 2015) - Poulsen, Mai Bang; Damgaard, Bodil; Zerahn, Bo; Overgaard, Karsten; Rasmussen, Rune Skovgaard
Abstract : Background and Purpose—: Poststroke fatigue is common and reduces quality of life. Current evidence for intervention is limited, and this is the first placebo-controlled trial to investigate treatment of poststroke fatigue with the wakefulness promoting drug modafinil. Methods—: The trial was randomized, double-blinded, and placebo-controlled. Patients were treated with 400-mg modafinil or placebo for 90 days. Assessments were done at inclusion, 30, 90, and 180 days. The primary end point was fatigue at 90 days measured by the Multidimensional Fatigue Inventory-20 general fatigue domain. Secondary end points included the Fatigue Severity Scale, the Montreal Cognitive Assessment, the modified Rankin Scale and the Stroke-specific quality of Life questionnaire. Adult patients with a recent stroke achieving a score of ≥12 on the Multidimensional Fatigue Inventory-20 general fatigue domain were consecutively included. Exclusion criteria were severe cognitive disabilities and contraindications for modafinil treatment. Results—: One thousand one hundred twenty-one patients with stroke were screened and 41 patients included, 21 received modafinil. The primary end point, the Multidimensional Fatigue Inventory-20 general fatigue score, did not differ between groups. Patients in the modafinil group obtained better scores on the Fatigue Severity Scale ( P =0.02) and in some subscales of the stroke-specific quality of life questionnaire (0.001< P <0.05), which were secondary outcomes. No serious adverse reactions were observed and there was no difference in blood pressure between groups. Conclusions—: There were no significant differences between the 2 groups with regard to the primary end point. There were secondary significant outcomes that should be explored in future trials. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01800097. Abstract : Supplemental Digital Content is available in the text.